The potential of sustainable building rating system in the Malaysian building industry - Shari, Zalina; Zaky Jaafar, Mohd Fakri; Salleh, Elias; Lim, Chin Haw (Faculty of Design & Architecture, Universiti Putra Malaysia, 2008)
A cursory glance at recent news headlines reveals growing problems in the Malaysian built environment, e.g., landslides, floods, environmental pollutions etc. On another front, the recent energy crisis also demands a re-look into the way we design, construct and operate our buildings. Various measures such as policies, regulations and environmental programmes have been adopted by the Malaysian government to resolve these issues: but these problems continue to exist. There is a growing acknowledgement throughout the world that a sustainable approach is a much-needed panacea to the many environmental crises. In the building industry, many countries around the world have introduced building assessment, rating and labeling systems to evaluate the environmental or sustainability performance of a building or development as one of the solutions. However, there is yet to be such effort in Malaysia. This paper explores the potential success of introducing and implementing SBRS (Sustainable Building Rating System) in Malaysia by using Trudgill’s AKTESP (Agreement, Knowledge, Technology, Economic, Social and Political) framework which identifies a number of common challenges for a better environment. The challenges are identified through existing literature, government initiatives and surveys. The paper concludes by suggesting some measures how these challenges might be overcome to ensure the success of SBRS in Malaysia.